The facts on file : dictionary of geology and geophysics - Lapidus, Dorothy Farris (New York : Facts On File Publications, 1987)
The concept of sea-floor spreading, the constant generation of new sea floor, offered a reason for why oceanic crust is younger than continental crust.
Keywords: HISTORICAL GEOLOGY